2019
DOI: 10.1080/21691401.2019.1626413
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Mirt2 functions in synergy with miR-377 to participate in inflammatory pathophysiology of Sjögren's syndrome

Abstract: Background: The interaction of long non-coding RNAs (lncRNAs)-microRNAs (miRs) exerts crucial functions in mediating inflammatory reaction. It is still unclear whether myocardial infarction associated transcript 2 (Mirt2)-miR-377 mediates the inflammatory pathogenesis in Sj€ ogren's syndrome (SS). Methods: The inflammatory lesion model was established by stimulating salivary gland epithelial cells (SGECs) by interferon gamma (IFN-c). Mirt2-and/or miR-377-transfected SGECs, as well as their negative controls, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…High levels of miR-155-5p have also been reported in inflammatory lesion models, such as cerebral ischemia-reperfusion injury (45). As previously reported, an inflammatory lesion model was established in SGECs by treatment with IFN-γ, where IFN-γ-treatment increased apoptosis and IL-6 and TNF-α mRNA expression (30).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…High levels of miR-155-5p have also been reported in inflammatory lesion models, such as cerebral ischemia-reperfusion injury (45). As previously reported, an inflammatory lesion model was established in SGECs by treatment with IFN-γ, where IFN-γ-treatment increased apoptosis and IL-6 and TNF-α mRNA expression (30).…”
Section: Discussionmentioning
confidence: 75%
“…In total, five mice were randomly selected from the 30 mice and the salivary glands were collected from the parotid, submandibular and sublingual glands. In accordance with previous research, SGECs were extracted from the salivary glands of five mice and pooled (30). Briefly, the salivary glands were washed 2-3 times with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Xin et al (5) demonstrated that lncRNA myocardial infarction associated transcript 2 (Mirt2) reduces apoptosis and inflammatory levels in interferon (IFN)-γ-induced inflammation in salivary gland epithelial cells. It is hypothesized that Mirt2 might block NF-κB, and Janus kinase (JAK)/STAT3 signaling by increasing miR-377 expression levels.…”
Section: Role Of Lncrnas In Oral Inflammatory Disordersmentioning
confidence: 99%
“…Numerous factors, including non-coding (nc)RNAs, leukocytes, cytokines and complement components, are involved in this process (2,3). Long non-coding (lnc)RNAs affect oral inflammation by sponging microRNAs (miRNA/miR) (4) or activating downstream target miRNAs (5). Research on competing endogenous (ce)RNA mechanisms, in which lncRNAs sponge specific miRNAs to suppress their target genes, has increased in numbers in over the last 2 years (6).…”
Section: Introductionmentioning
confidence: 99%